Effectiveness of Fertilization Techniques on Growth Two Varieties of Palm Oil Seeds (Elaeis guineensis Jacq.) in Main Nursery - Lubis, Erwin Junaidi; Rauf, Abdul; Sarifuddin, Sarifuddin (International Journal Labs, 2023)
This research was conducted to see the optimal level of fertilization in oil palms so that the macro and micronutrients are sufficient for the growth of oil palms. This research was carried out in the nursery area of ??the Soil Management Field Laboratory of the Indonesian Palm Oil Institute, Medan by observing soil characteristics. Soil analysis at the Soil, Plant, Fertilizer, and Water Laboratory at the Johor Agricultural Technology Study Center, North Sumatra, and the Analysis Laboratory at the Medan Oil Palm Research Center by observing soil analysis on chemical, physical, and cation exchange properties, as well as vegetative and fresh weight observations and dry plants. The study used a Completely Randomized Block Design where seedling height, stem circumference, number of leaf midribs, and leaf sheath length had the highest values ??in the sowing fertilization technique, as well as in the fresh weight of roots, shoots, and dry weight of roots, crowns also had the highest values ??in the sowing technique compared to sachets. and drip fertigation. This indicates that the growth and development of oil palm seedlings in the main nursery for PPKS 540 and SP-1 (Dumpy) varieties showed a positive response to the best growth increase in the sowing fertilization technique.